KEDUDUKAN JAKSA AGUNG PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 49/PUU-VIII/2010 DALAM PERSPEKTIF NEGARA HUKUM - Ahadi Fajrin Prasetya (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2019)
This writing aims to determine the basis for the consideration of the decision of the Constitutional Court Number 49/PUU-VIII /2010 on Article 22 Paragraph (1) letter d of Law Number 16 Year 2004 in the legal state prespective and to know the legal consequences of legal actions by the Attorney General before and after The Constitutional Court's decision. Using normative juridical research methods with prescriptive analysis. The conclusion of this writing is that the decision making number 49/PUU-VIII /2010 is based on the provisions of laws and regulations relating to the Constitutional Court, witnesses and experts presented by the petitioner and the government. The legal consequences of the Attorney General's actions prior to the Constitutional Court decision regarding the issuance of policies that brought legal consequences to the applicant in decision Number 49/PUU-VIII/2010 were valid and after the Constitutional Court decision, the position of Attorney General Hendarman Supanji was declared invalid, but the verdict could still be made Rejudicial review if there are constitutional reasons as regulated in the Regulation of the Constitutional Court Number 6 of 2005 concerning Guidelines for Procedures in Judicial Review Cases. Keywords : The Majestic Prosecutor Position, Decision Of The Constitusional Court, Legal State